Xanthan pyruvilation is essential for the virulence of Xanthomonas campestris pv. campestris - Bianco, María Isabel (2016)
Xanthan, the main exopolysaccharide (EPS) synthesized by Xanthomonas spp., contributes to bacterial stress tolerance and enhances attachment to plant surfaces by helping in biofilm formation. Therefore, xanthan is essential for successful colonization and growth in planta and has also been proposed to be involved in the promotion of pathogenesis by calcium ion chelation and, hence, in the suppression of the plant defense responses in which this cation acts as a signal. The aim of this work was to study the relationship between xanthan structure and its role as a virulence factor. We analyzed four Xanthomonas campestris pv. campestris mutants that synthesize structural variants of xanthan. We found that the lack of acetyl groups that decorate the internal mannose residues, ketal-pyruvate groups, and external mannose residues affects bacterial adhesion and biofilm architecture. In addition, the mutants that synthesized EPS without pyruvilation or without the external mannose residues did not develop disease symptoms in Arabidopsis thaliana. We also observed that the presence of the external mannose residues and, hence, pyruvilation is required for xanthan to suppress callose deposition as well as to interfere with stomatal defense. In conclusion, pyruvilation of xanthan seems to be essential for Xanthomonas campestris pv. campestris virulence.